Review of the subgenus Lophotyna Hampson of the genus Polymixis Hübner (Lepidoptera: Noctuidae: Noctuinae), with descriptions of two new species from Myanmar - Benedek, Balázs; Volynkin, Anton V.; Babics, János; Saldaitis, Aidas (Zootaxa, 2021)
The noctuid genus Lophotyna Hampson, 1910 is downgraded to a subgenus of the genus Polymixis Hübner, [1820] and reviewed. Two new species are described from Myanmar: Polymixis (Lophotyna) pateikkaya sp. nov. and Polymixis (Lophotyna) aungi sp. nov. The Polymixis crinomima (Wiltshire, 1946) species-group is associated with the subgenus Lophotyna. Polymixis crinomima diluta (L. Ronkay, Varga & Hreblay, 1998) syn.nov. is synonymized with P. crinomima crinomima (Wiltshire, 1946). Polymixis jabaliya (Wiltshire, 1987) is downgraded to a subspecies of P. crinomima: Polymixis crinomima jabaliya (Wiltshire, 1987), stat. nov. Four new combinations are established: Polymixis (Lophotyna) albosignata (Moore, 1881), comb. nov., Polymixis (Lophotyna) hoenei (Boursin, 1956), comb. nov., Polymixis (Lophotyna) albirena (Moore, 1867), comb. nov. and Polymixis (Lophotyna) khumbuensis (Owada, 1981), comb. nov. A replacement name, Polymixis (s. l.) boursinella nom. nov. is introduced for Polymixis (s. l.) albirena (Boursin, 1944), homonym nov. A lectotype for Mamestra albirena Moore, 1867 is designated.